2016
DOI: 10.1021/jacs.5b12530
|View full text |Cite
|
Sign up to set email alerts
|

Ultrathin Icosahedral Pt-Enriched Nanocage with Excellent Oxygen Reduction Reaction Activity

Abstract: Cost-efficient utilization of Pt in the oxygen reduction reaction (ORR) is of great importance for the potential industrial scale demand of proton-exchange membrane fuel cells. Designing a hollow structure of a Pt catalyst offers a great opportunity to enhance the electrocatalytic performance and maximize the use of precious Pt. Herein we report a routine to synthesize ultrathin icosahedral Pt-enriched nanocages. In detail, the Pt atoms were conformally deposited on the surface of Pd icosahedral seeds, followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
224
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 324 publications
(234 citation statements)
references
References 26 publications
6
224
0
4
Order By: Relevance
“…1e), which matches well with the three-dimensional (3D) model of icosahedron (inset in Fig. 1e) [37][38][39][40][41]. The XPS survey spectrum of Pt concave icosahedra (Fig.…”
Section: Resultssupporting
confidence: 78%
“…1e), which matches well with the three-dimensional (3D) model of icosahedron (inset in Fig. 1e) [37][38][39][40][41]. The XPS survey spectrum of Pt concave icosahedra (Fig.…”
Section: Resultssupporting
confidence: 78%
“…56,139 If a well-dened carbon support with a designable, high surface area, desired porous structure, designable high conductivity and controllable anti-corrosion becomes available, it would be very helpful for an understanding of the ORR mechanism and for practical applications. (4) Among the various Pt based catalysts exploited, shell-core Pt NPs show the most signicant potential as ORR catalysts because of their balance between activity and stability.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…Among these strategies, the approach to fabricate the Pt–M alloy catalysts has achieved significant progresses due to many advantages 7. By testing Pt alloy films with iron (Fe), cobalt (Co), and nickel (Ni), Nørskov and his co‐workers8 found that Pt 3 Co alloy film showed much higher ORR area activity than that of pure Pt.…”
Section: Introductionmentioning
confidence: 99%